Identifying the training load of soccer-related drills - Michaelides, M.; Petrov, D.; Parpa, K. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The purpose of the study was to determine the internal and external load of 2 popular drills used in soccer training. Specifically, the study examined a conditioned soccer game involving the ball possession time known as rondo and the small-sided game (SSG) drills.